Analyzing Jakarta Kini Platform Using the UTAUT 2 Model - Sutisna, Sutisna; Tricahyono, Dodie (International Journal Labs, 2023)
Jakarta Kini (JAKI) platform provides a seamless digital experience for various government services of DKI Jakarta, such as reporting/complaints, monitoring and accessing important information. This research aims to analyze the use and acceptance of JAKI using the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model, which consists of the variables Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit and Trust as the main variable. Along with Age and Gender as moderator variables. Data was collected from 400 respondents who had used the JAKI platform. The sampling method uses non-probability sampling and convenience sampling. The Partial Least Squares (PLS) technique is used to interpret and analyze the data using SmartPLS 4 software. Based on the analysis of this research, five direct variable relationships have a positive and significant effect. Habit and Trust variables positively and significantly affect Behavioral Intention and Use Behavior in using the platform. In moderate variables, only one variable has a significant effect. Age moderates the effect of Effort Expectancy on Behavioral Intention in using the platform.